Analisis Kebijakan Moneter Terhadap Daya Beli Masyarakat - Ovie Jaya Fitri; Muhammad Rafif Naufal; Saskia Zahratu Amami (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the impact of monetary policy on the purchasing power of society in Indonesia. Using a qualitative approach and secondary data from various official reports, this research examines the mechanism of monetary policy in controlling inflation and maintaining price stability, as well as its effect on the public’s ability to meet consumption needs. The results indicate that effective monetary policy can maintain price stability and preserve purchasing power, despite challenges such as commodity price volatility and exchange rate fluctuations. The study emphasizes the importance of coordination between monetary and fiscal policies as well as transparent communication in policy implementation to support societal welfare..